Pelatihan Pembuatan Eco Brick Menggunakan Bahan Sampah Plastik dan Kertas Bekas Sebagai Furnitur Kursi dan Meja Pada Peserta Didik SD Negeri Kedungbogo, Kecamatan Ngusikan - Sukma, Septi Ambar Indraningtia; Cahyono, Nor; Pangestu, Zilda; Mambausa’adah, Dewi; Mahfudzah, Aty; Hestiana, Annisa Dyah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
Ecobrick is a creative solution to reduce the amount of plastic waste disposed of in landfills and allows people to recycle plastic into useful materials. By filling plastic bottles with non-biological waste such as plastic until solid. The simple and easy-to-do manufacturing method can quickly spread to various communities. In this activity, using the experimental method, students experiment by making ecobricks using plastic waste and used paper as the main ingredients. The experimental method is a form of learning that involves tools and materials to achieve a goal. Through this experimental method, knowledge can be obtained and developed through experience in learning directly. The results of observations and discussions with teachers at Kedungbogo State Elementary School obtained information that in general, teachers want the waste found around them not only to become piles of waste that pollute the environment, but also to be recycled or reused into something more useful. Ecobrick making activities not only provide practical solutions to the problem of plastic waste, but also teach Kedungbogo State Elementary School students about the importance of recycling and environmental conservation. Through this activity, students can learn how to utilize plastic waste around them and turn it into something useful and valuable.